Project Based Learning and Dance Learning Outcomes in Islamic Schools - Elin Faiqotul Mu'arridloh; Warih Handayaningrum (Jurnal Pendidikan Sendratasik, 2025)
Arts and culture education, particularly dance, frequently faces the obstacle of monotonous, teacher-centered instruction and an imbalance between theory and practice, resulting in suboptimal student learning outcomes. This study aims to describe the implementation of the project based learning (PjBL) model and the resulting learning outcomes in cultural arts (dance) among twelfth-grade students at an Islamic-based madrasah whose movement vocabulary is deliberately constrained by religious values. A qualitative approach was employed, with data collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing, validated by source and technique triangulation. The findings show that PjBL implementation, carried out through the stages of essential questioning, project design, scheduling, progress monitoring, product presentation, and evaluation of the learning experience, was able to improve student learning outcomes across three domains: cognitive, psychomotor, and affective. Students demonstrated improved movement-analysis ability, motor skills synchronized with rhythm, and stronger teamwork and responsibility, all while preserving the propriety and religious values upheld by the school. The study affirms that PjBL can be contextually adapted as an effective model for creative dance instruction in Islamic educational settings with restricted movement vocabularies.